Efficacy and Safety of Low Frequency Whole-Body Electromyostimulation (WB-EMS) to Improve Health-Related Outcomes in Non-athletic Adults. A Systematic Review - Kemmler, Wolfgang; Weissenfels, Anja; Willert, Sebastian; Shojaa, Mahdieh; von Stengel, Simon; Filipovic, Andre; Kleinöder, Heinz; Berger, Joshua; Fröhlich, Michael (Frontiers in Physiology, 2018)
Exercise positively affects most risk factors, diseases and disabling conditions of middle to advanced age, however the majority of middle-aged to older people fall short of the exercise doses recommended for positively affecting cardio-metabolic, musculoskeletal and neurophysiological fitness or disabling conditions. Whole-Body Electromyostimulation (WB-EMS) may be a promising exercise technology for people unable or unmotivated to exercise conventionally. However, until recently there has been a dearth of evidence with respect to WB-EMS-induced effects on health-related outcomes. The aim of this systematic review is to summarize effects, limitations and risks of WB-EMS as a preventive or therapeutic tool for non-athletic adults. Electronic searches in PubMed, Scopus, Web of Science, PsycINFO, Cochrane and Eric were run to identify randomized controlled trials, non-randomized controlled trials, meta-analyses of individual patient data and peer reviewed scientific theses that examined (1) WB-EMS-induced changes of musculoskeletal risk factors and diseases (2) WB-EMS-induced changes of functional capacity and physical fitness (3) WB-EMS-induced changes of cardio-metabolic risk factors and diseases (4) Risk factors of WB-EMS application and adverse effects during WB-EMS interventions. Two researchers independently reviewed articles for eligibility and methodological quality. Twenty-three eligible research articles generated by fourteen research projects were finally included. In summary, thirteen projects were WB-EMS trials and one study was a meta-analysis of individual patient data. WB-EMS significantly improves muscle mass and -function while reducing fat mass and low back pain. Although there is some evidence of a positive effect of WB-EMS on cardio-metabolic risk factors, this aspect requires further detailed study. Properly applied and supervised, WB-EMS appears to be a safe training technology. In summary, WB-EMS represents a safe and reasonable option for cohorts unable or unwilling to join conventional exercise programs. However, much like all other types of exercise, WB-EMS does not affect every aspect of physical performance and health.